Aerospace series. Nuts, hexagon, slotted/castellated, self-locking, in steel, cadmium plated, MoS2 lubricated. Classification: 900 MPa (at ambient temperature)/235 °C. (9th March 2023) - British Standards Institution,
No abstract available